Congenital absence of sternum with tetralogy of Fallot, right aortic arch, and bilateral superior vena cava - Santosh Chavan; Nilima Narkhede; Rajaram Weling (SpringerOpen, 2023)
Abstract Background Congenital complete absence of sternal bone or cleft sternum or absent sternum is a very rare and potentially life-threatening birth defect. An association of cleft sternum with tetralogy of Fallot, right aortic arch, and bilateral superior vena cava is extremely rare, and not many cases have been reported. Case presentation A 2-year-old child was brought for routine checkup. He was a known case of congenital heart disease and midline thoracic defect at age of 3 months. Further investigations revealed absent sternum with tetralogy of Fallot, large cono-ventricular defect with bidirectional shunt, severe infundibular pulmonary stenosis, superiorly located right aortic arch, and bilateral superior vena cava. Conclusion Congenital absence of the sternum with intracardiac defects like tetralogy of Fallot with right aortic arch and bilateral superior vena cava is extremely rare malformation. Early diagnosis and surgical correction give the infant the best chance of survival.